Pre-Service Teachers' Perception Toward Environmental Knowledge, Attitudes and Behaviours (Malaysian Journal of Learning and Instruction, 2011)
Purpose â€“ The study investigated the environmental knowledge, attitudes and behaviours exhibited by the pre-service teachers and determined if there was any significant relationship between environmental knowledge, attitudes and behaviours. Method â€“ This descriptive study adopted a quantitative approach using questionnaires to obtain information on environmental knowledge (53 items with true/false responses), environmental attitudes (11 items with a 4-point Likert scale) and environmental behaviours (11 items with a 4-point Likert scale) of 173 3rd-year students enrolled in the Chemistry Teaching Methods course. Data were analysed using both descriptive statistics (frequency, percentage, mean and standard deviation) and inferential statistics(correlation coefficient). Findings â€“ The low total mean score on the environmental knowledge component indicated the respondentsâ€™ lack of knowledge on environmental issues especially in climate change, However, the respondents exhibited high positive environmental attitudes based on their responses to the relevant attitude items especially on items that related to adopting significant actions. Most of the items in the environmental behaviours component yielded considerably high mean scores which indicated a strong willingness on the part of the pre-service teachers to take pro-environmental behaviours. The findings also showed that there was no significant relationship between knowledge, attitudes and behaviours.